2004
DOI: 10.1300/j083v41n03_05
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 15. Ethical Practice Issues in Rural Perspective

Abstract: Community context has been viewed for more than two decades as the central organizing frame for rural social work practice. Ethical decision-making is complicated by multiple relationships with colleagues, caregiving family members, and elders that are common in rural areas. In order to address these complex situations, a model for multilevel contextual ethical analysis is proposed. The assumption that moral deliberations are based in social relationships is the foundation for contextual ethical analysis. An e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Access to sexual assault advocacy, criminal justice, and other services are compounded by the high frequency of dual relationships within rural communities (Davenport & Davenport, 1995;Healy, 2003). Logan, Evans, et al (2005) found that the degree of responsiveness of criminal justice and other systems was heavily politicized in rural communities.…”
Section: Response From Systems and Communitymentioning
confidence: 99%
See 3 more Smart Citations
“…Access to sexual assault advocacy, criminal justice, and other services are compounded by the high frequency of dual relationships within rural communities (Davenport & Davenport, 1995;Healy, 2003). Logan, Evans, et al (2005) found that the degree of responsiveness of criminal justice and other systems was heavily politicized in rural communities.…”
Section: Response From Systems and Communitymentioning
confidence: 99%
“…Distrust of outside help and a preference for informal support means that even when formal services are available, older adults might decline to use them. Affordability appears to be a factor in lack of services as well (Griffin, 1994;Healy, 2003), supported by evidence of a higher rate of poverty among older adults in rural areas (DeNavas-Walt et al, 2009). Services designed for the majority white, heterosexual population might not be appropriate or acceptable to rural African American elders (Griffin, 1994); elderly lesbian, gay, bisexual, and transgender persons (Healy, 2003); or other diverse groups.…”
Section: Lack Of Resourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although boundary violations (where the worker is manipulative, exploitive, coercive, or deceptive to the client) may occur in rural areas, boundary crossings may emerge more frequently. Boundary crossings refer to the mix of professional and personal relationships in which the anonymity of clients and workers can be unavoidably compromised (Healy, 2003). Rural areas include strong community ties with ample opportunity for chance encounters and boundary crossings with clients (Healy, 2003).…”
Section: Clinical Considerations and Guidelinesmentioning
confidence: 99%